1994
DOI: 10.2134/jeq1994.00472425002300040029x
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Simulator‐Grid Lysimeter System for Solute Transport Studies Using Large, Intact Soil Blocks

Abstract: A grid lysimeter system and sample collection, containment and storage techniques were developed for detailed laboratory studies of water and solute movement through intact soil blocks. This was done because existing designs and techniques had important deficiencies and were limited in their range of capabilities. Intact 46-cm soil cubes were isolated, then contained within a polyurethane foam shell, which formed a stable, intimate soil bond, was impermeable to water and strong enough to support a large soil b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Wang et al (1986) emphasized the role of holes and cracks in the profile on water flow and root distribution. Bowman et al (1994Bowman et al ( , 2003 reviewed the problem and found considerable water flowing down through a dry block of a soil profile in cracks and pores. Soil taxonomists knew about the problem all along but were somewhat intimidated by soil physicists from talking about it.…”
Section: History Of Cropping Systems' Models and Related Ongoing Resementioning
confidence: 99%
“…Wang et al (1986) emphasized the role of holes and cracks in the profile on water flow and root distribution. Bowman et al (1994Bowman et al ( , 2003 reviewed the problem and found considerable water flowing down through a dry block of a soil profile in cracks and pores. Soil taxonomists knew about the problem all along but were somewhat intimidated by soil physicists from talking about it.…”
Section: History Of Cropping Systems' Models and Related Ongoing Resementioning
confidence: 99%
“…The role of natural structural heterogeneity has recently been studied through the use of lysimeters and cores incorporating undisturbed soil (e.g. Bowman et al, 1994;Schoen et al, 1999;Bejat et al, 2000;de Rooij and Stagnitti, 2000;Strock et al, 2001). Studies have shown that a component of flow may move rapidly through discrete pathways termed 'preferential flow' (Luxmoore, 1981) attributed to soil structural, textural and hydraulic heterogeneities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, during periods when the evapotranspirational demand is high, soil moisture conditions inside the lysimeter are likely to be drier, due to the fact that upward transport of water from the underlying soil is cut off. Bowman et al (1994) overcame the zero-tension effect at the bottom boundary of their large block lysimeter by using an adjustable vacuum collector system to offset the 'perched water table effect', which prevented the accumulation of excess water at the lower boundary of the soil block.…”
Section: Causes Of Differences Between Laboratory and Field Lysimetermentioning
confidence: 99%